IR - SPECTRA ANALYSIS OF CARBON ADSORBENTS OBTAINED FROM MULBERRY STONE AND ROOT WASTE - Khaydarova, Shokhsanam Tolibjonovna; Isakov, Muhammedjan Yunusovich (SCIENCE and SOCIETY, 2026)
This in the article mulberry tree stems and roots secondary from raw materials based on taken carbonaceous adsorbents IR spectra analysis This is done . plant biomass physicist activate method using coal adsorbents prepared and their physical and chemical features infrared spectroscopy (FTIR) method analysis done. Obtained coal adsorbents functional groups learned. Obtained results this shows that high at temperature thermal and water steam with activated coal adsorbents on the surface organic functional groups amount decreases and microporosity structure harvest to do Coal adsorbents different industry processes, especially water and the air cleaning, industry waste neutralization such as in the fields application for new opportunities creates.